Comparative bioavailability of vitamins in human foods sourced from animals and plants - Chungchunlam SMS; Moughan PJ (Taylor and Francis Group, 2023)
Vitamins are essential components of enzyme systems involved in normal growth and function. The quantitative estimation of the proportion of dietary vitamins, that is in a form available for utilization by the human body, is limited and fragmentary. This review provides the current state of knowledge on the bioavailability of thirteen vitamins and choline, to evaluate whether there are differences in vitamin bioavailability when human foods are sourced from animals or plants. The bioavailability of naturally occurring choline, vitamin D, vitamin E, and vitamin K in food awaits further studies. Animal-sourced foods are the almost exclusive natural sources of dietary vitamin B-12 (65% bioavailable) and preformed vitamin A retinol (74% bioavailable), and contain highly bioavailable biotin (89%), folate (67%), niacin (67%), pantothenic acid (80%), riboflavin (61%), thiamin (82%), and vitamin B-6 (83%). Plant-based foods are the main natural sources of vitamin C (76% bioavailable), provitamin A carotenoid β-carotene (15.6% bioavailable), riboflavin (65% bioavailable), thiamin (81% bioavailable), and vitamin K (16.5% bioavailable). The overview of studies showed that in general, vitamins in foods originating from animals are more bioavailable than vitamins in foods sourced from plants.
Keywords: absorption; availability; bioavailability; digestibility; utilization; vitamin